Cross-cultural measurement invariance of the purpose in life test - Short form (PIL-SF) in seven Latin American countries - Caycho-Rodríguez, Tomás (2022)
The aim was to test the cross-cultural measurement invariance of the PIL-SF in a sample of people from seven Latin American countries. Additionally, the characteristics of the PIL-SF items were evaluated and to assess the relationship between purpose in life, as measured by the PIL-SF, and fear of COVID-19. A total of 4306 people from seven Latin American countries participated in the study. The results indicated that the PIL-SF is invariant in the seven participating countries and, therefore, there is evidence that the items reflect the purpose of life in the same way in all countries. This allows comparisons of purpose in life between countries that are free of bias, reflecting the true differences in how countries respond to items. From IRT, the discrimination parameters are adequate and indicate that the items cover a wide range of the purpose in life construct. The difficulty parameters are adequate and increase monotonically. This indicates that people would need a higher level of purpose in life to respond to the higher response categories. Thus, the PIL-SF items would be useful in determining people with a relatively high degree of purpose in life. Identifying people with different levels of purpose in life would allow them to be part of intervention programs, either to support those with low levels or to maintain and reinforce their purpose in life. The evidence of cross-country measurement invariance of the PIL-SF provides a measure to be used in cross-cultural studies about the meaning of life.